DOMESTIC ABUSE AND TRANSFORMATION IN ALICE WALKER’S NOVEL "THE COLOR PURPLE” - Hassooni Abdullah, Lecturer Rasha (Opción, 1970)
Alice Walker African American womanist whowon the Pulitzer Prize awarded for her fiction in 1983 for epistolarynovel The Color Purple (1982), she gives her voice to those who hadno voice. The color purple is a masterpiece of Alice walker focuses onthe struggle and discriminations of African American women on thehand of black and white men together .On the other hand, the novelshed the light on Celie, protagonist of the novel lost her mom and herinnocence to the man she call him Pa. She raped many times andconceived two children; hyper efficient house women who is highlyabused in a very violent domestic disturbance environment. Theimpact of her beloved sister Netti, she was Celie refuge as the novelgoes as series of letters. Methods: The researchers focus on the role ofthe family, society and how the male characters oppress anddiscriminate the women through the novel. Results: However theresearchers conclude how those women stand against the difficultiesand found their identity through unity and women- bonding andwomen should join together and support each other to reject maledominance and self-recognition. Conclusion: Thus, Shug tries andsupport Celie to identify herself as a creature, as a human being and asa black woman.